Juvenile justice in America - Bartollas, Clemens; Miller, Stuart J. (Prentice Hall, 1998)
This second edition aims to explore and define the emerging component of Juvenile Justice in the United States and the special challenges facing juvenile justice in the 1990s. Bartollas and Miller focus on the control, correction and treatment of both juvenile offenders and delinquents. The book describes the jobs and problems of those practictioners in the justice system who work with youths and the workings of the important components of the juvenile justice system that brings both together.